Do big prizes attract talent or big heads? The role of prize concentration, relative skill information, and narcissism in public and private tournament choice - Knox, Brian D.; Omer, Thomas C.; Stallings, Matthew A. (Accounting, Organizations and Society, 2026)
Prior accounting and economics research suggests that tournaments with highly concentrated prizes attract the most talented individuals. However, this research assumes that tournament entrants have granular, reliable information about their relative skill level. Using a laboratory experiment, we replicate this result: when relative skill information is available, prize concentration leads to skill-based selection. However, when relative skill information is unavailable, and tournament choice is public, we find that highly concentrated prizes instead attract more narcissistic individuals. Together, our results suggest that high-level positions with exceptionally large prizes can attract narcissistic applicants when entry decisions are publicly observable and relative skill information is limited. These findings inform both theory and practice by clarifying when tournament prize concentration selects for skill versus personality.